Association Between Artificial Liver Support System and Prognosis in Hepatitis B Virus-Related Acute-on-Chronic Liver Failure - Cui K; Liu CH; Teng X; Chen F; Xu Y; Zhou S; Yang Q; Du L; Ma Y; Bai L (Infection and Drug Resistance)
Kunping Cui, Chang-Hai Liu, Xiangnan Teng, Fang Chen, Yan Xu, Shaoqun Zhou, Qi Yang, Lingyao Du, YuanJi Ma, Lang Bai Center of Infectious Diseases, West China Hospital of Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of ChinaCorrespondence: YuanJi Ma; Lang Bai, Center of Infectious Diseases, West China Hospital of Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China, Tel +86-02885422650 ; +86-18980602254, Email maxe.doc@163.com; pangbailang@163.comObjective: The artificial liver support system (ALSS) has been recruited as an available method for patients with acute-on-chronic liver failure (ACLF), but its impact on the outcome of ACLF remains controversial. This study aimed to investigate the association between ALSS treatment and short-term prognosis of hepatitis B-related ACLF (HBV-ACLF).Methods: This was a retrospective observational cohort study, and data were obtained from the Center of Infectious Diseases, West China Hospital of Sichuan University, between Mar 2015 and December 2021. The primary outcome was 28-day transplant-free mortality and the secondary outcomes were 60- and 90-day transplant-free mortality. Patients were divided into standard medical therapy (SMT) and ALSS groups. Kaplan-Meier survival analysis curves show the 28-day, 60-day and 90-day transplant-free mortality. Based on the feature selection result of univariate logistic, univariate Cox and Boruta algorithm, the univariate and multivariate logistic and COX regression models were used to investigate the association of ALSS with 28-day, 60-day and 90-day outcomes in patients with HBV-ACLF. Subgroup analyses were conducted to test the robustness of the results.Results: A total of 589 hBV-ACLF patients were enrolled in this study (median age, 48.00 years [IQR,44.00– 55.00 years]; 70 [11.9%] female). The 28-day, 60-day and 90-day transplant-free mortality rates were 25.6%, 35.8% and 38.9%, respectively. In the univariate and Kaplan-Meier survival analysis, ALSS could significantly reduce 28-day, 60-day and 90-day transplant-free mortality compared to SMT. Furthermore, an in-depth analysis of our study revealed that the therapeutic benefits of the ALSS were observed exclusively within the end-stage (PT-INR ≥ 2.5) subgroup of HBV-ACLF patients.Conclusion: Compared to SMT, ALSS demonstrated efficacy primarily in enhancing the short- term prognosis of end-stage HBV-ACLF patients, rather than across the entire spectrum of HBV-ACLF patients.Keywords: artificial liver support systems, hepatitis B-related acute-on-chronic liver failure, prognosis